2009
DOI: 10.1055/s-0029-1237389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Conditioning on Salivary IgA and Plasma IgA, IgG and IgM in Older Men and Women

Abstract: As people age, they experience a decline in immune responses. Unusually heavy acute or chronic exercise could increase the risk of upper respiratory tract infection (URTI) whereas regular moderate physical activity may reduce URTI symptomatology. The purpose of the present study was to determine whether an aerobic exercise program would promote chronic adaptations in plasma IgA, IgG and IgM, and salivary IgA (Sal-IgA) in both elderly women and men. Forty-three independently living men and women, aged between 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
1
18
0
3
Order By: Relevance
“…A previous study found that a 12-month mixed protocol based on endurance and resistance training improved salivary IgA levels in elderly subjects (4). Similarly, Martins et al (12) concluded that 16 weeks of aerobic training significantly increased salivary IgA in older men and women. In this regard, it should be emphasized that our exercise intervention program lasted just 12 weeks and that continued activity by participants would be desirable.…”
Section: Discussionmentioning
confidence: 92%
“…A previous study found that a 12-month mixed protocol based on endurance and resistance training improved salivary IgA levels in elderly subjects (4). Similarly, Martins et al (12) concluded that 16 weeks of aerobic training significantly increased salivary IgA in older men and women. In this regard, it should be emphasized that our exercise intervention program lasted just 12 weeks and that continued activity by participants would be desirable.…”
Section: Discussionmentioning
confidence: 92%
“…23,24 In athletes, a decrease in IgA levels is only seen at times of greater intensity of training, making the athlete less resistant to pathogenic microorganisms and increasing the susceptibility to upper respiratory tract infections. 23,24 In athletes, a decrease in IgA levels is only seen at times of greater intensity of training, making the athlete less resistant to pathogenic microorganisms and increasing the susceptibility to upper respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…En conclusión, los estudios anteriores reflejan que se necesita por lo menos 4 a 12 meses para encontrar cambios significativos en las concentraciones séricas y salivales de IgA 15,[17][18][19] . En términos generales, el presente trabajo de investigación tuvo por objetivo establecer los efectos de un programa de hidrogimnasia sobre las concentraciones séricas de IgA, en adultas mayores.…”
Section: Discussionunclassified
“…El ejercicio aerobio en la modalidad de danza, durante 19 semanas en adultos mayores, se tradujo en incrementos significativos en comparación con el grupo control. Otro estudio con el mismo diseño metodológico pero con una duración mayor (32 semanas) demostró aumento significativo en las concentraciones de IgA 17 . Investigaciones donde refieren la combinación de ejercicios de resistencia a la fuerza y actividades aerobias encontraron diferencias significativas respecto al grupo control 18 .…”
Section: Artículo Originalunclassified